2015
DOI: 10.2147/prbm.s80642
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems in anxious and depressive older adults

Abstract: PurposeThe objective of this study was to identify the sleep problems most often encountered by the elderly according to the presence or absence of anxiety and mood disorders. The aim was also to determine whether groups of anxious, depressive, and asymptomatic individuals differ in relation to sleep onset latency; awakenings at night or early in the morning; subjective quality of sleep; taking of sleep medication; and daytime sleepiness.MethodsStructured interviews based on the DSM-IV-TR were administered to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 58 publications
1
17
0
1
Order By: Relevance
“…First, among a national sample of older adults, respondents with high anxiety symptoms had significantly greater odds of sleeping medication use compared to older adults with low anxiety symptoms, even after adjusting for potential confounding. Second, we replicated previous findings that have associated depressive symptoms with sleeping medication use (Potvin et al , 2014; Omvik et al , 2010; Leblanc et al , 2015; Vaidya et al , 2014). Third, a greater number of chronic health conditions, worse self-rated health, being female and White were also associated with increased odds of using sleeping medications.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…First, among a national sample of older adults, respondents with high anxiety symptoms had significantly greater odds of sleeping medication use compared to older adults with low anxiety symptoms, even after adjusting for potential confounding. Second, we replicated previous findings that have associated depressive symptoms with sleeping medication use (Potvin et al , 2014; Omvik et al , 2010; Leblanc et al , 2015; Vaidya et al , 2014). Third, a greater number of chronic health conditions, worse self-rated health, being female and White were also associated with increased odds of using sleeping medications.…”
Section: Discussionsupporting
confidence: 86%
“…Studies of older adults living outside of U.S. have inconsistently identified anxiety symptoms as a predictor of sleeping medication use (Potvin et al , 2014; Leblanc et al , 2015; Omvik et al , 2010). One study among the U.S. general population did associate anxiety and sleeping medications, though did not identify age as a significant factor (Vaidya et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 20% of people with insomnia suffer from major depression ( 5 ), yet 69% of people with depression have mild or moderate insomnia ( 6 , 7 ). It is widely recognized that insomnia may serve as a useful warning signal, because of the frequent occurrence of insomnia before a bout of depression strikes ( 8 , 9 , 10 , 11 ).…”
mentioning
confidence: 99%
“…It has generally been shown that noise roughly causes 11% to 20% of arousals and awakenings during sleep [12]. It is established that anxiety disorders are also associated with interrupted sleep [13]; a better nights' sleep and the concurrent lowered anxiety leads to quicker recovery and better satisfaction of the patients. Kirk conducted a study in a hospice in England and he found that a majority of patients preferred room with single occupancy as it offered more privacy, less ambient noise, better quality of sleep, less embarrassment and also because family members could stay without upsetting other patients [13].…”
Section: Discussionmentioning
confidence: 99%